Somatic Mutations Profile of a Young Patient With Metastatic Urothelial Carcinoma Reveals Mutations in Genes Involved in Ion Channels - Sharma, Jyoti; Deb, Barnali; George, Irene A.; Kapil, Shruthi; Coral, Karunakaran; Kakkar, Nandita; Pattanaik, Smita; Mandal, Arup Kumar; Mavuduru, Ravimohan S.; Kumar, Prashant (Frontiers in Oncology, 2019)
Background: Urothelial carcinoma is the most common malignancy of the bladder and considered as primarily a disease of the elderly. Studies addressing bladder tumor occurrence in young age group are rare. Case presentation: A 19-year-old male presented with gross total painless haematuria. Histology after biopsy revealed high-grade transitional cell carcinoma with lymph node metastasis. The patient succumbed to the disease on the day 72 of the treatment. Here, we used whole-exome sequencing of paired tumor-normal sample to identify somatic mutations and possible targets of treatment. Result: We predicted eight potential driver mutations (TP53 p.V157L, RB1 c.1498+1G>T, MED23 p.L1127P, CTNND1 p.S713C, NSD1 p.P2212A, MED17 p.G556V, DPYD p.Q814K and SPEN p.S1078*). In addition, we predicted deleterious mutations in genes involved in the ion channels (CACNA1S p.E1581K, CACNG1 p.P71T, CACNG8 p.G404W, GRIN2B p.A1096T, KCNC1 p.G16V, KCNH4 p.E874K, KCNK9 p.R131S, P2RX7 p.A296D and SCN8A p.R558H). Conclusions: Most likely, mutations in genes involved in ion channels may be responsible for the aggressive behaviour of tumor. Ion channels are the second largest class of drug targets, thus may serve as a putative potential therapeutic targets in advanced stage urothelial carcinoma.